1991
DOI: 10.1007/bf01042182
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic variability within individual fibres of the cat tibialis posterior and diaphragm muscles

Abstract: Variance in succinate dehydrogenase activity along the transverse and longitudinal axes of fibres from the cat tibialis posterior and diaphragm muscles was determined in order to estimate the three-dimensional distribution of mitochondria within single fibres. The variance (coefficient of variation) in succinate dehydrogenase activity along the transverse fibre axis was greatest in type IIB fibres from both muscles. Intracellular compartmentalization (i.e. subsarcolemmal vs central core differences in succinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The between-day mean differences for measurements increased by ,-,0.1% for a sample of ,-~50 fibres and by ,--0.5% for a single fibre. The between-trials difference in SDH activity determined within-day and between-day is likely to be due, in part, to the possibility that SDH activity may vary along the length of muscle fibres (Nemeth et al, 1981;Blanco et al, 1988Blanco et al, , 1991. The estimated distance between the groups of sections for the within-and between-day measurements was 70-100 ~m and 200-250 ~m, respectively.…”
Section: Reliability Of the Histochemical Sdh Measurementmentioning
confidence: 91%
“…The between-day mean differences for measurements increased by ,-,0.1% for a sample of ,-~50 fibres and by ,--0.5% for a single fibre. The between-trials difference in SDH activity determined within-day and between-day is likely to be due, in part, to the possibility that SDH activity may vary along the length of muscle fibres (Nemeth et al, 1981;Blanco et al, 1988Blanco et al, , 1991. The estimated distance between the groups of sections for the within-and between-day measurements was 70-100 ~m and 200-250 ~m, respectively.…”
Section: Reliability Of the Histochemical Sdh Measurementmentioning
confidence: 91%
“…In this regard, methods were developed to quantify both actomyosin ATPase and succinate dehydrogenase activities (35, 37, 275). Using these quantitative techniques, a number of studies have shown that the metabolic properties of diaphragm muscle fibers are continuous and highly plastic under a variety of conditions (36, 204, 237, 377, 381, 389, 390, 466). …”
Section: Respiratory Muscle Structurementioning
confidence: 99%
“…Five muscle samples each of YC and YT group and four muscle samples each of MC and MT group were used. The staining protocol used has been described previously (Martin et al 1985, Blanco et al 1991. Sections 10-µm-thick (four sections per muscle) were incubated in a medium containing 100 m phosphate buffer, pH 7.6 ; 0.75 m sodium azide ; 1 m 1methoxyphenazine methylsulfate (mPMS) ; 1.5 m nitroblue tetrazolium (NBT) ; 5 m EDTA (disodium salt) ; and 48 m succinate (disodium salt).…”
Section: Histochemical Procedures For Succinate Dehydrogenase (Sdh) Amentioning
confidence: 99%